EVALUASI PENGGUNAAN METODE NON TANGGUL DAN TANGGUL PADA LAHAN REKLAMASI PENGEMBANGAN TERMINAL PETI KEMAS PELABUHAN TANJUNG MAS SEMARANG - Ranggi Sanggawuri; Defri Maulana; YI Wicaksono; Wayudi Kushardjoko (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
There are limitations on the land development in TPKS lead to make reclamation land with non levee and levee method.The strength of steel pile and batter pile structure construction in each method will be analyzed using Plaxis 2D. The analysis result from Plaxis 2D are safety factor and structure force. The result from first variation uses non levee method has safety factor about 1,27 and has additional cost about Rp.3,880,854,789 from contract (second B variation); the result from second A variation uses levee method with dredging until – 9 m has safety factor about 1,4203 and save the cost about Rp.1,193,035,512 from contract (second B variation); the result from second B variation uses levee method with dredging until – 12,5 m has safety factor about 1.3387 and cost equal to contract about Rp. 211,090,224,932; the result from third variation uses levee method with add geotextile has safety factor about 1,6614 and has additonal cost about Rp.1,233,863,485 from contract (second B variation); the result from fourth variation uses levee method with add anchor has safety factor about 2,3044 and has additional cost about Rp.3,963,658,400 from contract (second B variation). Comparation between non levee method and levee method has result that levee method is better than non levee method.